Non-violent communication in teacher-student dialogue in the educational process - Korobchanska, A.; Kolisnik, I.; Lutenko, M. (Харківський національний медичний університет, 2025)
Students experience stress, anxiety, and tension. In these conditions, it is important not only to help the student survive these negative states, but also to continue their studies and personal growth. The current main tasks of education are to educate a comprehensively developed, self-sufficient individual who is able to realize himself, find his place in life, strives for self-improvement throughout life, and has developed abilities for constructive communication. Students acquire the necessary competencies during their studies. Instead, there are important cross-curricular skills that are formed and improved at all levels of education, such as the ability to work in a team, learn to study, get along with others, and the ability to manage one’s emotions. We see that these are the soft skills that employers are looking for today. Among the top 10 skills that will be needed in 2025 are endurance, stress resistance and flexibility
Keywords: 2025а